IGF-1 boosts mitochondrial function by a Ca2+ uptake-dependent mechanism in cultured human and rat cardiomyocytes - Sánchez-Aguilera, Pablo; López-Crisosto, Camila; Norambuena-Soto, Ignacio; Penannen, Christian; Zhu, Jumo; Bomer, Nils; Hoes, Matijn F.; Van Der Meer, Peter; Chiong, Mario; Westenbrink, B. Daan; Lavandero, Sergio (Frontiers in Physiology, 2023)
A physiological increase in cardiac workload results in adaptive cardiac remodeling, characterized by increased oxidative metabolism and improvements in cardiac performance. Insulin-like growth factor 1 (IGF-1) has been identified as a critical regulator of physiological cardiac growth, but its precise role in cardiometabolic adaptations to physiological stress remains unresolved. Mitochondrial calcium (Ca2+) handling has been proposed to be required for sustaining key mitochondrial dehydrogenase activity and energy production during increased workload conditions, thus ensuring the adaptive cardiac response. We hypothesized that IGF-1 enhances mitochondrial energy production through a Ca2+-dependent mechanism to ensure adaptive cardiomyocyte growth. We found that stimulation with IGF-1 resulted in increased mitochondrial Ca2+ uptake in neonatal rat ventricular myocytes and human embryonic stem cell-derived cardiomyocytes, estimated by fluorescence microscopy and indirectly by a reduction in the pyruvate dehydrogenase phosphorylation. We showed that IGF-1 modulated the expression of mitochondrial Ca2+ uniporter (MCU) complex subunits and increased the mitochondrial membrane potential; consistent with higher MCU-mediated Ca2+ transport. Finally, we showed that IGF-1 improved mitochondrial respiration through a mechanism dependent on MCU-mediated Ca2+ transport. In conclusion, IGF-1-induced mitochondrial Ca2+ uptake is required to boost oxidative metabolism during cardiomyocyte adaptive growth.